(untitled) (Mantichora. Italian Journal of Performance Studies, 2022)
During its historical development, the Western dance tradition has transformed its traditional aesthetic models of reference, reconfiguring, particularly during the 20th century, its relationship with the world and other arts’ poetics through experimental models and continuous hybridizations. This contribution analyses the phenomenal relation between the dance in contemporary authorial creations - with reference to Alessandro Sciarroni’s poetics - and images, references, traditions that are part of the spectator’s cultural heritage: a memorial practice that projects itself towards the future, through archetypes and recurring schemes. The path travels from the production of an artist fully included in the ‘third landscape’ (Pontremoli, 2018) of the dance to the analysis of a choreic practice, accomplished through recurrent images. The concept of schêmata is the foundation of artistic perception in Western culture: we thus aim to analyze the power of images as a powerful engine of movement between the recovery of collective memories and the re-evaluation of the participatory role of the spectator.